Generalized Rough Fuzzy Ideals in Quantales. (16th January 2018) - Qurashi, Saqib Mazher; Shabir, Muhammad
Abstract : The paper examines the generalized rough fuzzy ideals of quantales. There are some intrinsic relations between fuzzy prime (primary) ideals of quantales and generalized rough fuzzy prime (primary) ideals of quantales. Homomorphic images of "generalized rough ideals, generalized rough prime (primary) ideals, and generalized rough fuzzy prime (primary) ideals" which are incited by quantale homomorphism are examined.